2011
DOI: 10.4061/2011/315879
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fructose on Renal Function and Blood Pressure

Abstract: Fructose is a sugar present in sucrose, high-fructose corn syrup, honey, and fruits. Fructose intake has increased markedly in the last two centuries, primarily due to increased intake of added sugars. Increasing evidence suggests that the excessive intake of fructose may induce fatty liver, insulin resistance, dyslipidemia, hypertension, and kidney disease. These studies suggest that excessive intake of fructose might have an etiologic role in the epidemic of obesity, diabetes, and cardiorenal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 55 publications
(74 reference statements)
0
17
1
Order By: Relevance
“…It was suggested, that rodents show a lesser rise in serum UA in response to fructose due to the presence of uricase in their liver and hence lower serum UA than humans (Stavric et al, 1976). In our study, the consumption of the high-fat diet enriched with 20% of fructose for 3 weeks did not result in the rise of plasma UA, in both healthy and nephrectomized pigs, that is in contrast to results reported in previous studies (Kretowicz et al, 2011;Johnson et al, 2013b).…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…It was suggested, that rodents show a lesser rise in serum UA in response to fructose due to the presence of uricase in their liver and hence lower serum UA than humans (Stavric et al, 1976). In our study, the consumption of the high-fat diet enriched with 20% of fructose for 3 weeks did not result in the rise of plasma UA, in both healthy and nephrectomized pigs, that is in contrast to results reported in previous studies (Kretowicz et al, 2011;Johnson et al, 2013b).…”
Section: Discussioncontrasting
confidence: 97%
“…For example, Gersch et al (2007) showed that administration of fructose to rats with reduced renal function (the remnant kidney model) can accelerate the progression of renal disease, resulting in worse proteinuria, glomerulosclerosis, and tubulointerstitial fibrosis. Other authors reported no effect of low-fructose diet for a period of 6 weeks on renal function of humans with stable chronic kidney disease (Kretowicz et al, 2011). As mentioned, fructose can increase intracellular and circulating UA levels due to increased nucleotide turnover and synthesis, as well as due to stimulation UA synthesis from amino acid precursors, such as glycine (Johnson et al, 2013b).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Increased total fructose consumption has been implicated in the obesity epidemic [4] and contributes to the rising frequency of cardiorenal metabolic syndrome (CRS)-associated insulin resistance, type 2 diabetes mellitus, and hypertension (Fig. 1) [5, 6]. Recent data from the third National Health and Nutrition Examination Survey (NHANES) indicate that consumption of sugar-sweetened beverages is significantly associated with plasma uric acid (UA) concentrations [7].…”
Section: Introductionmentioning
confidence: 99%
“…There is more than one explanation for decreasing the body weight in HFD consumption in this study. It is interesting that rats feed on HFD may not show an increase in overall body weight if it is not associated with diets high in fat [32]. Excessive consumption of fructose is accompanied by a decrease in body weight because of excessive muscle wasting and wastage of tissue protein due to renal failure.…”
Section: Discussionmentioning
confidence: 99%